Adverse Histological Features of Differentiated Thyroid Cancer Are Commonly Found in Autopsy Studies: Implications for Treatment Guidelines - Robenshtok, Eyal; Neeman, Bar; Reches, Liran; Ritter, Amit; Bachar, Gideon; Kaminer, Keren; Shimon, Ilan; Mizrachi, Aviram (Thyroid (New York, N.Y.), 2022)
While the popularity of lobectomy for differentiated thyroid cancer (DTC) has increased since the 2015 ATA (American Thyroid Association) guidelines, recent studies reported that adverse histological features (minimal extrathyroidal extension [mETE], multifocality, vascular invasion, and lymph node [LN] metastases) may be found in 30-60% of lobectomy specimens, questioning the validity of this approach. To assess the prevalence adverse histological features in occult DTC detected in autopsy studies. Meta-analysis of autopsy studies of the thyroid in subjects without known history of thyroid cancer. Twenty-nine studies including 8750 subjects fulfilled the inclusion criteria, with incidentally discovered DTC in 740 autopsies (8.5%). Age was reported in 17 studies, with a median age of 61 years (range 41-68 years). Multifocality was reported in 27 studies with a calculated event rate of 28.2% ([CI 23.1-33.8], = 46.3%), with bilateral involvement in 18% [CI 12.6-25.1]. mETE was reported in 5 studies, with an event rate of 24.5% ([CI 9.3-50.7], = 88.5%), and the presence of LN metastases were reported in 13 studies with an event rate of 11% ([CI 6.1-19.1], = 69.5%). Vascular invasion was reported in seven studies with an event rate of 16% ([CI 4-47], = 86.8%). Of 25 studies with whole body autopsies (722 subjects), 3 cases of distant metastases were reported, of which 2 had fatal metastatic disease (where thyroid origin was not diagnosed before death), and 1 had occult disease. Adverse histological features including mETE, LN metastases, multifocality, and vascular invasion are common in occult DTC. When minimal in size, these adverse histological features do not seem to be markers of aggressive disease and may not be an indication for completion thyroidectomy or radioiodine therapy.